Development of a Multi-Component Biosensor for Recombinase Polymerase Amplification-CRISPR/Cas12a-Based Detection of Fusarium oxysporum f. sp. cubense tropical race 4 - Madufor, Ndubuisi Johnkennedy (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.